Exploring duration-based methods of estimating interest rate sensitivity of bonds: With application in the Philippine government bond - Busto, Nancy Grace F. (Animo Repository, 2017)
Duration is widely used by financial analysts as a measure of sensitivity of bonds to changes in interest rate. It is commonly used by fund managers to substitute interest rate risk of their assets and liabilities. A number of fixed income sensitivity indicators, including the price value of a basis point (PV01) and the yield value of a price change are established within the duration framework (Fabozzi, 2005; Hillier et al. 2011). Furthermore, the simplicity and intuitive interpretation of duration has made it a popular interest management tool for treasury managers for bond analysis, investment strategies and portfolio management. However, it is well known that the convexity of the price-yield relationship introduces approximation errors that grow as changes in yield increases.. In this study, the proponent proposed a new approach to measure interest rate sensitivity of bonds, which significantly improved the accuracy of the Traditional Duration method and achieved a level of precision close to the other existing approaches such as Traditional Duration plus Convexity, Exponential Duration and Discrete Duration. The study also showed through simulations and stress testing that the proposed method outperformed other methodologies proposed in previous literature.